Diversified modification strategies for sodium alginate-based probiotic-embedded gels and their potential for food applications - Kaili Wang; Wenjia Zhou; Jianing Zhai; Peng Du; Libo Liu; Shuang Li; Aili Li (Food Science of Animal Products)
Sodium alginate (SA), due to its unique biodegradability and gel-forming properties, is used as an excellent wall material. It can achieve targeted delivery of probiotics into the body for the purpose of improving human microecology. However, SA hydrogels alone tend to have weak mechanical properties and are susceptible to external environmental attack, making it difficult to adequately protect the probiotic core. In order to overcome this bottleneck, in recent years, there have been literature reports on the modification of SA-based hydrogels based on physical, chemical, and synergistic modification of both. And other novel wall materials were introduced to be blended with SA to form a composite wall material with a denser structure and superior performance, which enhances the resistance and storage period stability of probiotics. Based on this, this paper outlines the structural properties and advantages and disadvantages of SA, and systematically summarises the effects and differences of different modification methods on the performances of SA-based microcapsules. It also meticulously combs out the wide application of SA-based probiotic microcapsules in the field of food, showing its great potential in improving food quality and promoting health. Finally, this paper objectively points out the problems and challenges facing the current research on SA-based microencapsulation delivery system. It provides new perspectives and strategies for the upgrading of the wall material of SA-based microencapsulation and the improvement of the efficiency of the probiotic delivery system.